The Time Structure of Investment Behavior in United States Manufacturing, 1947-1960 - Jorgenson, Dale W.; Stephenson, James A. (The Review of Economics and Statistics, 1967)
Dale W. Jorgenson, James A. Stephenson, The Time Structure of Investment Behavior in United States Manufacturing, 1947-1960, The Review of Economics and Statistics, Vol. 49, No. 1 (Feb., 1967), pp. 16-27